Analisis Kebangkrutan Dengan Menggunak Metode Altman Z-Score, Springate, Dan Internal Growth Rate Pada Pelaku Ekonomi Kreatif Subsektor Fashion PT. Matahari Department Store Tbk Periode 2014-2018 - Fahma Diena Achmada; Jeni Susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract PT Matahari Department Store Tbk is the largest retail company in Indonesia and has been registered as the excecutant of creative economy in the fashion subsector. The rise of news about open-close outlets having done by the company makes researcher is very enthusiastic to examine how the actual financial performance and the potential for bankruptcy when it is viewed on their financial report. This study aims to determine the potential for bankruptcy using the Altman Z-Score method, the Springate method, and the Internal Growth Rate method on the retail company as the excecutant of creative economy in the subsector of fashion, namely PT Matahari Department Store Tbk in the 2014-2018 period. The type used in this research is quantitative descriptive. There are three methods used in this research, which are Altman Z-Score, Springate, and Internal Growth Rate to analyze the ratio produced by using the methods. The results showed that PT Matahari Department Store Tbk did not have the potential to go bankrupt or be declared a healthy company during the period 2014-2018. This study also used the Kruskal Wallis Test to find out the comparison among the three methods used and the result showed that there is significant difference got from these methods. Keywords: Bankruptcy, Altman Z-Score, Springate, Internal Growth Rate, and Creative Economy